New Publications Of The Bureau Of Mines - List 942 - November-December 1995 ? Electronic Information (The National Institute for Occupational Safety and Health (NIOSH), 1995)
Many USBM research and information products are available through the systems or formats listed below: Mines FaxBack: Return fax service. 1. Use the touch-tone handset attached to your fax machine's telephone jack. (ISDN [digital] telephones cannot be used with fax machines.) 2. Dial 202/219-3644 3. Listen to the menu options and punch in the number of your selection, using the touch-tone telephone 4. After completing your selection, press the start button on your fax machine. Mines Data: Computer bulletin board. Log on via modem through 202/501-0373, or call 202/501-0406 for technical assistance. CD-ROM: This USBM disk is updated quarterly and sold by GPO's Superintendent of Documents. For information on the latest product, please contact Rodger Wedgeworth, 202/501-9557. Internet/World Wide Web: Text and graphics. Access via PC-based browsing software such as Netscape or Mosaic. Universal Resource Locator (URL) is: http:/www.usbm.gav Internet/Gopher Server: Text and tables only. Using Gopher client software, access via port 70 as follows: gopher.usbm.gav Internet System Administrator: webmaster®usbm.gov (or contact your local System Administrator).